Predicting major cardiac and cerebrovascular events in acute coronary syndrome patients using the thyroid hormone sensitivity index - He, Hui; Wang, Jun; Xia, Long; Ye, Tao; Luo, Yan; Chen, Qiang; Feng, Qiao; Peng, Xiufen; Jiang, Maoling; Liu, Hanxiong; Xiang, Tao; Xiong, Shiqiang; et al. (Frontiers in Endocrinology, 2025)
Background and aimThe thyroid hormone sensitivity index provides a new perspective for investigating nuanced alterations in thyroid function in cardiovascular disorders. However, the predictive value of thyroid hormone sensitivity indices for adverse events following percutaneous coronary intervention (PCI) in acute coronary syndrome (ACS) patients remains unknown. This study aimed to investigate the predictive value of thyroid sensitivity indices for major adverse cardiac and cerebrovascular events (MACCEs) in these patients.Methods and resultsA total of 431 patients were included in the analysis. Thyroid hormone sensitivity indices were calculated using the thyroid-stimulating hormone index (TSHI), thyrotrophic thyroxine resistance index (TT4RI), thyroid feedback quantile-based index (TFQI), and parametric thyroid feedback quantile-based index (PTFQI). During the median follow-up period, 50 (11.60%) patients experienced MACCEs. Multivariate Cox regression analysis revealed that TSHI (HR 1.277, 95% CI 1.110–1.468, P<0.001), TT4RI (HR 1.002, 95% CI 1.001–1.003, P<0.001), TFQI (HR 1.130, 95% CI 1.043–1.224, P=0.003), and PTFQI (HR 1.237, 95% CI 1.107–1.383, P<0.001) were independent predictors of MACCEs. The area under the ROC curve (AUROC) revealed that PTFQI had the highest predictive value (AUROC =0.688, 95% CI: 0.595–0.780; P < 0.001). Adding PTFQI to the GRACE score can enhance the risk prediction of MACCEs in ACS patients undergoing PCI, AUROC = 0.759 (95% CI 0.676-0.842, P < 0.001) vs AUROC = 0.646 (95% CI 0.563-0.729, P = 0.001), and there is a significant difference (P = 0.0108). Subgroup analysis indicated that PTFQI had a more significant predictive value for MACCEs in males and patients with abnormal blood glucose.ConclusionThyroid hormone sensitivity indices are associated with a greater risk of MACCEs in patients with ACS following PCI.